2023
DOI: 10.3390/biology12050742
|View full text |Cite
|
Sign up to set email alerts
|

The Migration and the Fate of Dental Pulp Stem Cells

Abstract: Human dental pulp stem cells (hDPSCs) are adult mesenchymal stem cells (MSCs) obtained from dental pulp and derived from the neural crest. They can differentiate into odontoblasts, osteoblasts, chondrocytes, adipocytes and nerve cells, and they play a role in tissue repair and regeneration. In fact, DPSCs, depending on the microenvironmental signals, can differentiate into odontoblasts and regenerate dentin or, when transplanted, replace/repair damaged neurons. Cell homing depends on recruitment and migration,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 124 publications
(149 reference statements)
0
1
0
Order By: Relevance
“…The pulp tester electrode transmits electrical impulses to the pulp primarily through the fluid in the tubules; as the distance between the two entities decreases, the resistance to the flow of electric current decreases correspondingly [ 18 ]. These findings support the current study, which found that the mesiobuccal cusp tip closest to the corresponding pulp horn below had a lower electric response [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pulp tester electrode transmits electrical impulses to the pulp primarily through the fluid in the tubules; as the distance between the two entities decreases, the resistance to the flow of electric current decreases correspondingly [ 18 ]. These findings support the current study, which found that the mesiobuccal cusp tip closest to the corresponding pulp horn below had a lower electric response [ 19 ].…”
Section: Discussionmentioning
confidence: 99%